2014
DOI: 10.1016/j.jaac.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Abnormalities and Cognitive Impairment in Early-Onset Schizophrenia-Spectrum Disorders

Abstract: OBJECTIVE To characterize white matter abnormalities in adolescents with early onset schizophrenia (EOS) relative to three comparison groups (adolescents at clinical high risk for developing schizophrenia [CHR], adolescents with cannabis use disorder [CUD], and healthy controls [HC]), and to identify neurocognitive correlates of white matter abnormalities in EOS. METHOD We used diffusion tensor imaging and tractography methods to examine fractional anisotropy (FA) of the cingulum bundle, superior longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 52 publications
4
50
1
Order By: Relevance
“…47 Our observation of FA reductions in the right CT is in line with findings in patients with early-onset schizophrenia and in individuals at high risk for psychosis. 48 However, deficits in this region are less frequently observed in later stages of illness, suggesting that FA changes in the CT may be more prominent at the time of illness onset.…”
Section: Discussionmentioning
confidence: 99%
“…47 Our observation of FA reductions in the right CT is in line with findings in patients with early-onset schizophrenia and in individuals at high risk for psychosis. 48 However, deficits in this region are less frequently observed in later stages of illness, suggesting that FA changes in the CT may be more prominent at the time of illness onset.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased FA in the left IFOF predicts worse neurocognitive performance both in never-medicated chronic schizophrenia [46] and in adolescents with earlyonset schizophrenia [47] , as well as predicting empathic impairments in patients with schizophrenia [48] . Other whitematter fiber tracts related to the PFC in schizophrenia include the anterior limb of the internal capsule, the medial portion of which includes the anterior thalamic radiation linking the thalamus and the PFC [49,50] , the genu of the corpus callosum linking the bilateral PFCs [51,52] , and deep white matter within the PFC [53] .…”
Section: Arcuate Fasciculusmentioning
confidence: 99%
“…DTI facilitates the in vivo study of brain white matter (WM) microstructure (Mori et al, 2008), and typical DTI measures include fractional anisotropy (FA), mean (MD), axial (AD) and radial diffusivity (RD). Alterations in these metrics are reported in 22q11DS (Barnea-Goraly et al, 2003; da Silva Alves et al, 2011; Deng et al, 2015; Kates et al, 2015; Kikinis et al, 2012; Martin et al, 2014; Ottet et al, 2013; Padula et al, 2015; Radoeva et al, 2012; Scariati et al, 2016; Sundram et al, 2010; Villalon-Reina et al, 2013), and some of the patterns observed are similar to deficits in SZ (Kyriakopoulos et al, 2008; Roalf et al, 2015; Thomason and Thompson, 2011), adolescents with psychosis (Davenport et al, 2010; White et al, 2007) and youth at risk for developing psychosis (Epstein et al, 2013; Lee et al, 2013). In contrast to structural gray matter findings, DTI results in 22q11DS are more inconsistent.…”
Section: 0 Introductionmentioning
confidence: 81%
“…Patients with 22q11DS who develop schizophrenia have similar symptoms compared to patients with idiopathic schizophrenia (Murphy et al, 1999). Indeed, both 22q11DS and idiopathic schizophrenia share brain morphological changes (Eliez et al, 2001; Eliez et al, 2000; Glahn et al, 2008; Jalbrzikowski et al, 2013; Schaer et al, 2006), including alterations in WM structure and organization (Asami et al, 2014; Epstein et al, 2013; Kyriakopoulos et al, 2008; Lee et al, 2013; Roalf et al, 2013b). Thus, direct comparison of WM differences between 22q11DS patients with and without psychotic symptoms may elucidate deficits specific to psychosis.…”
Section: 0 Introductionmentioning
confidence: 99%